Conductivity studies on plasticised PEO/Chitosan proton conducting polymer electrolyte - Majid, Siti Rohana; Arof, Abdul Kariem; Kadir, M.F.Z.A.; Teo, L.P. (Springer Verlag (Germany), 2009)
The effect of ethylene sulphite (ES) content on the conductivity, morphology and nature of polymer electrolytes based on polyethylene oxide (PEO) and chitosan blend doped with ammonium nitrate (NH(4)NO(3)) has been analysed in this study. The films produced by the solution cast technique were kept in a desiccator filled with silica gel before characterisation. The sample (23.8 wt-% PEO+35.7 wt-% chitosan) 239.7 wt-% NH(4)NO(3)-0.8 wt-% ES exhibited the highest room temperature conductivity of the order 10(-4) s cm(-1). The conductivity-temperature relationship was found to obey Arrhenius rule. The activation energy for the highest conducting sample is 0.02 eV. From Jonscher's universal power law, the trend of exponent s v. temperature showed that the conduction mechanism of the ions in the highest conducting sample can be explained by the quantum mechanical tunnelling (QMT) model. Scanning electron microscopy (SEM) revealed that surfaces of samples containing ES are porous.